Analysis of Increasing Understanding of Biology Learning through the Integration of Religious Values at the SMA/MA Level in Jambi Province - Aty Mulyani (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to explain the increased understanding of integrating religious values in Biology Learning at the SMA/MA level in Jambi Province. In this study, 31 biology teachers at the MA level were involved with the classification of five male teachers and 26 female teachers as respondents in Jambi province using a closed questionnaire. Based on the results of the questionnaire that the researchers distributed to 31 respondents, the results obtained were 1) The percentage of effort in the learning process that could be integrated with religious values was 90.3% 2) The percentage of learning difficulties integrated with religious values tended to be religious values themselves by 8.1%; 3) The percentage of integrating religious values with science is carried out simultaneously at 54.8%; 4) The percentage of integrating religious values needs special guidance of 67.7%; 5) The percentage of integration of religious values with science is believed to be able to instill religious character by 93.5%; 6) ) The percentage of integration of religious values with science is believed to be able to deepen understanding of science by 87.1%; 7) The percentage of integration of religious values with science is believed to be able to expand understanding of science by 90.3%; 8) The percentage of integration of religious values with science is believed to strengthen faith in their religion by 93.5%. Based on these data it can be concluded that the integration of religious values requires specific guidelines so that they can be used to guide the process of integrative learning of religious values, which are useful for deepening and broadening students' understanding of science.